2018
DOI: 10.1016/j.schres.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Impaired social cognition in schizophrenia during the Ultimatum Game: An EEG study

Abstract: We suggest that the difference found in the FRN amplitude is associated with difficulties of patients in interpreting another's behavior. Although schizophrenic patients correctly activate neuronal bases in the proposer condition, they were not able to activate the same networks in the responder condition, thereby exposing their difficulties in social interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…If the responder accepts the proposal, money is shared accordingly and both win money. However, if the responder refuses, both players end up with (Horat et al, 2017). Classically, the game ends after the responder’s decision (Guth et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the responder accepts the proposal, money is shared accordingly and both win money. However, if the responder refuses, both players end up with (Horat et al, 2017). Classically, the game ends after the responder’s decision (Guth et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…It presented as a smiling or frowning face in the proposer condition, whereas the smiley was neutral in the responder condition. This figure has been adapted from Horat et al (2017). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG signal is a non-stationary time series. It can be analyzed in time domain by extracting features such as standard deviation, skewness, peak mean absolute value of the signal or by using event-related potential (ERP) [19]. Frequency domain features also should be paid attention to.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, facial recognition ability falls into the first domain, social perception. While patients with schizophrenia show deficits in all three domains [ 6 , 34 , 35 ], previous studies have consistently demonstrated that the lack of facial emotion recognition is related to reduced temporal lobe volume. In particular, a review stated that abnormalities in face processing in schizophrenia are strongly associated with structural abnormalities in regions such as fusiform gyrus, superior temporal sulcus, amygdala and prefrontal cortex [ 36 ].…”
Section: Introductionmentioning
confidence: 99%